Correlation between Lgr5 Expression and 5-FU based Chemotherapy Response in Stage IV Colorectal Cancer Patients - Kgs. M. Rosyidi; Mediarty Syahrir; Suly Auline Rusminan; Legiran (HM Publisher, 2021)
Background. Colorectal cancer is the third commonest malignancy and the second leading cause of cancer death in the world. 5-Fluorouracyl-based chemotherapy is the primary treatment modality for colorectal cancer. Cancer stem cells are known to be responsible for chemotherapy resistance. Lgr5 is a colorectal cancer stem cell marker that is the target gene for Wnt signaling. Lgr5 potentiates the Wnt signaling pathway through inhibition of a regulator that inhibits Wnt signaling. Lgr5 overexpression is associated with a worse prognosis and chemotherapy resistance. This study was aimed to investigate the correlation between Lgr5 expression and 5-FU-based chemotherapy response in stage IV colorectal cancer patients at Dr. Mohammad Hoesin Hospital Palembang.Methods. This study used a correlative analysis study with a retrospective design using secondary data from medical records and paraffin blocks of stage IV colorectal cancer patients who received 5-FU-based chemotherapy from September 2018 to September 2020. The number of samples was 30 subjects consisting of 22 cases of negative responses and eight positive responses. All samples were stained with Lgr5 immunohistochemistry. Data analysis used the contingency coefficient correlation test.Results. Of the 30 research subjects, 20 subjects (66.7%) had high Lgr5 expression and ten subjects (33.3%) with low Lgr5 expression. Correlation analysis using the contingency coefficient test showed a weak correlation between Lgr5 expression and 5-FU based chemotherapy response with a positive direction, which means the higher the Lgr5 expression, the less response to chemotherapy.Conclusion. There is a weak correlation between Lgr5 expression and 5-FU based chemotherapy response in stage IV colorectal cancer patients at dr.Mohammad Hoesin Hospital Palembang.